ANALYSIS OF THE INFLUENCE OF SOCIAL MEDIA AND FINANCIAL LITERACY ON THE INVESTMENT BEHAVIOR OF THE MILLENNIAL GENERATION WITH FEAR OF MISSING OUT (FOMO) AS A MEDIATING VARIABLE IN NORTH LUWU REGENCY - Tompo, Edi; Anshar, Muh.Ashary; Syam, Andi Faisal (Yayasan Education and Social Center, 2026)
This study aims to analyze the influence of work motivation, competence, and leadership on employee performance with job satisfaction as a mediating variable. The research approach uses a quantitative method with a survey design on respondents selected through a purposive sampling technique. Data were collected using a structured questionnaire and analyzed using the Partial Least Squares-based Structural Equation Modeling (PLS-SEM) method. The results show that work motivation, competence, and leadership have a positive and significant effect on employee job satisfaction and performance. In addition, job satisfaction is proven to significantly mediate the relationship between the independent variables and performance. These findings indicate that improving employee performance does not only depend on individual factors, but is also greatly influenced by the quality of leadership and a conducive work environment. The implications of this study emphasize the importance of integrated human resource management through strengthening motivation, improving competency, and developing transformational leadership to create sustainable satisfaction and performance. This research is expected to serve as a reference for policymakers and practitioners in designing effective and adaptive human resource development strategies.